Hepatic hydatid cyst presenting as cutaneous abscess - Islam, MN; Khan, NA; Haque, SS; Hossain, M; Ahad, MA (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):165-169 The abstract of this article is available on the PubMed website